2016
DOI: 10.1002/jsfa.7862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcuma longa rhizome powder on egg quality, performance and some physiological indices of laying hens fed different levels of metabolizable energy

Abstract: An improvement in the productive performance of laying hens fed high-energy diets might be associated with decreasing health indices and product quality, which could potentially be amended by nutritional modifications such as incorporating medicinal herbs in the feed. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
5
18
0
Order By: Relevance
“…For instance, Kermanshahi and Riasi (2006) indicate a decrease of 63.9, 50.2 and 63.3% for TAG, total-and LDL-cholesterol levels, respectively, while HDL-cholesterol content was raised up to 15%. Similar results were obtained by many other authors (e.g., Malekizadeh et al, 2012;Riasi et al, 2012;Arshami et al, 2013;Saraswati et al, 2013;Mirbod et al, 2017). Concerning enzyme activities, Malekizadeh et al (2012) found that AST and ALT activities decreased by 5.1 and 19.0%, in line with the results of Mirbod et al (2017) and Saraswati et al (2013).…”
Section: Feeding Trials Using Trp In Conjunction With Other Active Agsupporting
confidence: 86%
See 2 more Smart Citations
“…For instance, Kermanshahi and Riasi (2006) indicate a decrease of 63.9, 50.2 and 63.3% for TAG, total-and LDL-cholesterol levels, respectively, while HDL-cholesterol content was raised up to 15%. Similar results were obtained by many other authors (e.g., Malekizadeh et al, 2012;Riasi et al, 2012;Arshami et al, 2013;Saraswati et al, 2013;Mirbod et al, 2017). Concerning enzyme activities, Malekizadeh et al (2012) found that AST and ALT activities decreased by 5.1 and 19.0%, in line with the results of Mirbod et al (2017) and Saraswati et al (2013).…”
Section: Feeding Trials Using Trp In Conjunction With Other Active Agsupporting
confidence: 86%
“…On the other hand, TRP improves laying hen immunity, since it increases total immunoglobulins (Ig) and IgG titers after sheep red blood cells (SRBC) injections (Arshami et al, 2013), and TRP boosted the immune response to NDV and SRBC antigens, although feeding TRP also decreased the heterophils:lymphocytes ratio (Mirbod et al, 2017). Another interesting effect of TRP supplementation is a decrease of E. coli counts in the ileal content of farmed laying hens (Mirbod et al, 2017).…”
Section: Feeding Trials Using Trp In Conjunction With Other Active Agmentioning
confidence: 99%
See 1 more Smart Citation
“…The ileal samples were completely mixed, poured into sterile tubes, stored in an ice‐covered box, and instantly transferred to the laboratory. The ileal content was prepared to culture on Eosin Methylene Blue agar plates (Merck, Darmstadt, Germany), and the microflora populations were counted and confirmed using biochemical tests of indole, methyl red, Voges‐Proskauer, and citrate reactions as previously explained by Mirbod, Mahdavi, Samie, and Mehri ().…”
Section: Methodsmentioning
confidence: 99%
“…The effects of dietary treatments on intestinal cell morphology were evaluated using the method described in Mirbod et al. (). In brief, two randomly selected birds from each pen were compassionately sacrificed at the end of the trial.…”
Section: Methodsmentioning
confidence: 99%